Tính giá trị biểu thức
a. 25 496 + 28 212 : 4 b. ( 108 610 - 87 352 ) : 3
tính giá trị biểu thức
a)\(\sqrt{2-\sqrt{3}}\)\(\left(\sqrt{6}+\sqrt{2}\right)\)
b)\(\dfrac{x-25}{\sqrt{x}-5}\)-\(\dfrac{4+4\sqrt{x}+x}{\sqrt{x}+2}\)với x\(\ge\)0 ; x\(\ne\)25
\(\sqrt{2-\sqrt{3}}\left(\sqrt{6}+\sqrt{2}\right)=\sqrt{4-2\sqrt{3}}\left(\sqrt{3}+1\right)=\sqrt{\left(\sqrt{3}-1\right)^2}\left(\sqrt{3}+1\right)\)
\(=\left|\sqrt{3}-1\right|\left(\sqrt{3}+1\right)=\left(\sqrt{3}-1\right)\left(\sqrt{3}+1\right)=3-1=2\)
\(\dfrac{x-25}{\sqrt{x}-5}-\dfrac{x+4\sqrt{x}+4}{\sqrt{x}+2}=\dfrac{\left(\sqrt{x}-5\right)\left(\sqrt{x}+5\right)}{\sqrt{x}-5}-\dfrac{\left(\sqrt{x}+2\right)^2}{\sqrt{x}+2}\)
\(=\sqrt{x}+5-\left(\sqrt{x}+2\right)=5-2=3\)
a: Ta có: \(\sqrt{2-\sqrt{3}}\cdot\left(\sqrt{6}+\sqrt{2}\right)\)
\(=\sqrt{4-2\sqrt{3}}\cdot\left(\sqrt{3}+1\right)\)
\(=\left(\sqrt{3}-1\right)\left(\sqrt{3}+1\right)\)
=3-1
=2
b: Ta có: \(\dfrac{x-25}{\sqrt{x}-5}-\dfrac{x+4\sqrt{x}+4}{\sqrt{x}+2}\)
\(=\sqrt{x}+5-\sqrt{x}-2\)
=3
Tính một cách hợp lí giá trị của biểu thức
A = (-25).8.2.5.(-4).13
B = 13.(-7)+(-13).57+13.(-36)
A = (-25).8.2.5.(-4).13 = [(-25).(-4)].8.2.5.13 = 100.8.10.13 = 10400
B = 13.(-7) + (-13).57 + 13.(-36) = 13.(-7) - 13.57 + 13.(-36)
= 13.[(-7) + (-57) + (-36)]
= 13. (-100)
= -1300
Ta có: \(A=\left(-25\right)\cdot8\cdot2\cdot5\cdot\left(-4\right)\cdot13\)
\(=\left[\left(-25\right)\cdot\left(-4\right)\right]\cdot\left(2\cdot5\right)\cdot\left(8\cdot13\right)\)
\(=104000\)
Ta có: \(B=13\cdot\left(-7\right)+\left(-13\right)\cdot57+13\cdot\left(-36\right)\)
\(=13\cdot\left(-7\right)-13\cdot57-13\cdot36\)
\(=13\left(-7-57-36\right)\)
\(=13\cdot\left(-100\right)=-1300\)
tính nhanh
a/ A= 119+(-213)+212+(-118)+2009
b/ B=223+132+187-23-32-87
c/ C= -2012+(-596)+(-201)+496+301
d/ D= -329+(15-101)-(25-440)
a/ A= 119+(-213)+212+(-118)+2009
A= ! - 1 + 2009
A= 2009
b/ B=223+132+187-23-32-87
B = 200 + 100 + 100
B = 400
c/ C= -2012+(-596)+(-201)+496+301
C = -2012 - 100 + 100
C = -2012
d/ D= -329+(15-101)-(25-440)
D = 0
hok tốt!!!
\(a,A=119+\left(-213\right)+212+\left(-118\right)+2009\)
\(A=\left(119+212+2009\right)+\left[\left(-213\right)+\left(-118\right)\right]\)
\(A=2340+\left(-331\right)\)
\(A=2009\)
\(b,B=223+132+187-23-32-87\)
\(B=\left(223+132+187\right)+\left(-23-32-87\right)\)
\(B=542-142\)
\(B=400\)
1. Tính giá trị biểu thức
A, 3 242 + 2 326 + 192
B, 520 401 + 27 429 - 13 965
C, 13 228 - ( 28 073 - 16 785 )
D, 86 572 - ( 58 406 + 9 275 )
A. 3,242 + 2,326 + 192 = 5,760
B. 520,401 + 27,429 - 13,965 = 534,865
C. 13,228 - (28,073 - 16,785) = 2,940
D. 86,572 - (58,406 + 9,275) = 18,891
a: \(3242+2326+192\)
\(=3242+192+2326\)
\(=3434+2326=5760\)
b: \(520401+27429-13965\)
\(=\left(520401+27429\right)-13965\)
\(=547830-13965=533865\)
c: \(13228-\left(28073-16785\right)\)
\(=13228+16785-28073\)
\(=\left(13228+16785\right)-28073\)
\(=30013-28073=1940\)
d: \(86572-\left(58406+9275\right)\)
\(=86572-67681\)
=18891
Tính giá trị của biểu thức
a)1/3+1/4-1/6
b)2/5x5/7:3/4
a. 1/3 + 1/4 - 1/6
= 7/12 - 1/6
= 5/12
b. 2/5 x 5/7 : 3/4
= 2/7 : 3/4
= 8/21
Tính giá trị biểu thức
a) 123,15 – 23,15 x 4 b) 18,64 – 8,64 : (12,2 + 12,8)
a: \(123,15-23,15\cdot4\)
\(=100+23,15-23,15\cdot4\)
\(=100-23,15\cdot3\)
\(=100-69,45=30,55\)
b: \(18,64-8,64:\left(12,2+12,8\right)\)
\(=18,64-8,64:25\)
\(=18,64-8,64\cdot0,04\)
\(=10+8,64-8,64\cdot0,04\)
\(=10+8,64\cdot0,96=10+8,2944=18,2944\)
Tính giá trị biểu thức
a) 7/5 x 3/4 : 4/5 = ........................................
= ........................................
Tìm x:
b) x - 3/9 = 8/7
a) 21/20 : 4/5
= 21/16
b) x = 8/7+3/9
x = 31/21
2.tính giá trị biểu thức
a) 1/3 + 4/3 nhân 1/2
b) 3/5 nhâ 4/7 : 16/21
a) \(\dfrac{1}{3}+\dfrac{4}{3}\times\dfrac{1}{2}=\dfrac{1}{3}+\dfrac{4}{6}=\dfrac{1}{3}+\dfrac{2}{3}=\dfrac{3}{3}=1\)
b) \(\dfrac{3}{5}\times\dfrac{4}{7}:\dfrac{16}{21}=\dfrac{3}{5}\times\dfrac{4}{7}\times\dfrac{21}{16}=\dfrac{12}{35}\times\dfrac{21}{16}=\dfrac{252}{560}=\dfrac{9}{20}\)
Bài 1: So sánh
a) \(-2^{30}\) và \(-3^{30}\)
b) \(35^5\) và \(6^{10}\)
Bài 2: Tính giá trị biểu thức
a) \(\dfrac{\left(-3\right)^{10}.15^5}{25^3.\left(-9\right)^7}\)
b) \(\left(8x-1\right)^{2x+1}=5^{2x+1}\)
\(1,\\ a,2< 3\Rightarrow2^{30}< 3^{30}\Rightarrow-2^{30}>-3^{30}\\ b,6^{10}=6^{2\cdot5}=\left(6^2\right)^5=36^5>35^5\left(36>35\right)\)
\(2,\\ a,\dfrac{\left(-3\right)^{10}\cdot15^5}{25^3\cdot\left(-9\right)^7}=\dfrac{3^{10}\cdot5^5\cdot3^5}{5^6\cdot3^{14}}=\dfrac{3}{5}\\ b,\left(8x-1\right)^{2x+1}=5^{2x+1}\\ \Leftrightarrow8x-1=5\\ \Leftrightarrow x=\dfrac{3}{4}\)
Bài 2:
a: Ta có: \(\dfrac{\left(-3\right)^{10}\cdot15^5}{25^3\cdot\left(-9\right)^7}\)
\(=\dfrac{-3^{10}\cdot3^5\cdot5^5}{5^6\cdot3^{14}}\)
\(=-\dfrac{3}{5}\)
b: Ta có: \(\left(8x-1\right)^{2x+1}=5^{2x+1}\)
\(\Leftrightarrow8x-1=5\)
\(\Leftrightarrow8x=6\)
hay \(x=\dfrac{3}{4}\)
Bài 1:
a: \(-2^{30}=-8^{10}\)
\(-3^{30}=-27^{10}\)
mà 8<27
nên \(-2^{30}>-3^{30}\)
b: \(35^5=35^5\)
\(6^{10}=36^5\)
mà 35<36
nên \(35^5< 6^{10}\)